Glucose‐mediated regulation of glycerol uptake in Rhodosporidium toruloides: Insights through transcriptomic analysis on dual substrate fermentation. Issue 3 (2nd June 2016) - Bommareddy, Rajesh Reddy; Sabra, Wael; Zeng, An‐Ping
Abstract : Rhodosporidium toruloides is a robust oleaginous yeast that can accumulate lipids to more than 70% of its dry cell mass. Even though it is extensively studied for its fermentation of substrates like glucose and glycerol, limited information is available about its metabolism of mixture of glucose and glycerol. During growth on mixture of glucose and glycerol a typical diauxic growth and higher lipid yields were observed. To understand this phenomenon, RNA‐seq analysis was implemented to study the gene expression profiles during growth on mixtures mainly to elucidate regulation of glycerol metabolism. Insights into lipid biosynthesis on mixed substrates are provided at a systems level. Among others, transcriptional profiles showed that glycerol might be produced intracellularly and glycerol kinase (GUT1) and glycerol 3–phosphate dehydrogenase (GUT2) enzymes were not downregulated in the presence of glucose. Transcriptional analysis also showed that the regulation of glycerol uptake in the presence of glucose at transcriptional level is different from that observed in Saccharomyces cerevisiae .